The clinical application of laparoscope-assisted peritoneal vaginoplasty for the treatment of congenital absence of vagina. Issue 3 (June 2016) - Qin, Chenglu; Luo, Guangnan; Du, Min; Liao, Shi; Wang, Chunping; Xu, Keke; Tang, Jie; Li, Baoyan; Zhang, Juanjuan; Pan, Hongxin; Ball, Tyler W.; Fang, Yujiang
Abstract: Objective: To evaluate the outcomes of laparoscope-assisted peritoneal vaginoplasty for the treatment of congenital vaginal atresia. Methods: A retrospective study enrolled patients diagnosed with congenital vaginal atresia who were treated with one of two different laparoscope-assisted peritoneal vaginoplasty techniques (named Luohu-one and Luohu-two) between October 31, 2001 and December 31, 2014. Operative time, intraoperative bleeding volume, surgical difficulty, complications, and post-procedure sexual satisfaction were reported. Results: Data were collected for 620 patients. The Luohu-one procedure was used in the treatment of 145 patients, while 475 patients were treated with the Luohu-two procedure. In 5 (0.8%) patients, it was necessary to perform a sigmoid colon vaginoplasty. During surgery, 16 patients experienced a rectal injury, among whom, 9 patients experienced a rectal–vaginal fistula. Follow-up data extending to 7 years were available for 285 patients. Of these 285 patients, 231 agreed to report details of their sexual experiences. In total, 222 (96.1%) patients reported being very satisfied with their vaginal conditions and sex life. The Luohu-two procedure demonstrated shorter operative and recovery time, and reduced intraoperative bleeding. However, both procedures demonstrated satisfactory results. Conclusion: Laparoscope-assisted peritoneal vaginoplasty demonstrated good safety and effectiveness in the treatment of patients with congenital vaginal atresia.